2020
DOI: 10.1155/2020/2930347
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Biomarkers of Squamous Cell Carcinoma of the Aerodigestive Tract: A Systematic Review and Quality Assessment

Abstract: Introduction. Aerodigestive squamous cell carcinomas (ASCC) constitute a major source of global cancer deaths. Patients typically present with advanced, incurable disease, so new means of detecting early disease are a research priority. Metabolite quantitation is amenable to point-of-care analysis and can be performed in ASCC surrogates such as breath and saliva. The purpose of this systematic review is to summarise progress of ASCC metabolomic studies, with an emphasis on the critical appraisal of methodologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…At the same time, simplicity is also one of its advantages, which can guide clinicians to evaluate the disease progression and prognosis more conveniently and accurately ( Ferrè et al, 2016 ; Schmitt and Chang, 2016 ; Peng et al, 2017 ; Kopp and Mendell, 2018 ). Our prognostic model aimed to determine the association between prognosis and basic characteristics and should be accurate and economical ( Iasonos et al, 2008 ; Balachandran et al, 2015 ; König et al, 2017 ; Goh et al, 2020 ). The nomogram included multiple independent variables and was easy for clinicians to evaluate the results and choose individual treatments for LUSC patients.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, simplicity is also one of its advantages, which can guide clinicians to evaluate the disease progression and prognosis more conveniently and accurately ( Ferrè et al, 2016 ; Schmitt and Chang, 2016 ; Peng et al, 2017 ; Kopp and Mendell, 2018 ). Our prognostic model aimed to determine the association between prognosis and basic characteristics and should be accurate and economical ( Iasonos et al, 2008 ; Balachandran et al, 2015 ; König et al, 2017 ; Goh et al, 2020 ). The nomogram included multiple independent variables and was easy for clinicians to evaluate the results and choose individual treatments for LUSC patients.…”
Section: Discussionmentioning
confidence: 99%
“…One important caveat to using metabolic biomarkers for LC diagnosis was introduced in a systematic review of SCC of the aerodigestive tract [ 48 ]. Goh et al found that the various classes of metabolites (branch chain amino acids, fatty acids, amino acids, carbohydrates, inorganic compounds, and lipids) showed considerable overlap in expression in LSCC, oesophageal SCC, and head and neck SCC, though predominantly between OSCC and HNSCC.…”
Section: Metabolic and Inflammatory Biomarkersmentioning
confidence: 99%
“…As analytical technologies become more advanced, salivary biomarkers derived from genomics, transcriptomics, proteomics, microbiomics, and metabolomics have been reported as biomarkers for the clinical screening and detection of LC. [5][6][7][8][9][10] However, most of these studies analyzed differences between LC and controls, and there are not many reports that discriminate LC from benign lung lesions (BLL). 11,12 To the best of our knowledge, there has only been one study based on salivary metabolomic approaches for the discrimination of LC from BLL.…”
Section: Introductionmentioning
confidence: 99%
“…However, human saliva is increasingly being used as a diagnostic specimen for various diseases, because its collection is convenient and non‐invasive. As analytical technologies become more advanced, salivary biomarkers derived from genomics, transcriptomics, proteomics, microbiomics, and metabolomics have been reported as biomarkers for the clinical screening and detection of LC 5–10 . However, most of these studies analyzed differences between LC and controls, and there are not many reports that discriminate LC from benign lung lesions (BLL) 11,12 .…”
Section: Introductionmentioning
confidence: 99%